A new species of Bryobiinae (Acari: Tetranychidae) and first report of Aplonobia eurotiae (Mitrofanov & Strunkova) from Turkey - Cobanoglu, Sultan; Ueckermann, Edward A.; Cilbircioglu, Cihan (Systematic and Applied Acarology Society, 2021)
The Bryobiinae (Acari: Tetranychidae) of Turkey are reviewed and presented here. The distribution and habitats of these species are provided. A new Bryobia species, Bryobia cagani sp. nov., is described based on four females which were collected on grass and lettuce in a garlic field located at Kastamonu. Aplonobia eurotiae (Mitrofanov & Strunkova) (Acari, Tetranychidae) is reported for the first time in Turkey, based on specimens collected on a Pinus sp. (Pinaceae) from the Nemrut Mountains close to Adıyaman. Aplonobia eurotiae is re-described and an identification key to the Turkish species of Bryobiinae and world species of Aplonobia is presented.